Extraction, Characterization, and Impact of Polysaccharides From Zhonghuang No. 1 Etiolated‐Green Tea on Human Fecal Microbiota - Baoming Tian; Xue Zhou; Shuo Pan; Wei Liu (Food Bioengineering)
ABSTRACT Tea polysaccharides have attracted widespread attention in regulating gut microbiota. A highly efficient enzymolysis and ultrasonic‐assisted extraction method was developed and optimized for the extraction of polysaccharides from Zhonghuang No. 1 etiolated‐green tea (GTP) with a‐single factor and response surface methodology, i.e, with a pH of 5.5, an enzyme concentration of 7%, an ultrasonic time of 2.5 h, a solid‐liquid ratio of 1:20 g/mL, and an ultrasonic temperature of 80°C. GTP exhibited a triple helix structure and demonstrated the ability to bind with Congo red. Its surface was observed to be spherical with slender chain fragments. GTP remained intact throughout the simulated in vitro digestive process, which encompassed the oral, gastric, and small intestinal phases. The relative abundance of Bacteroidota was significantly increased, while the Firmicutes/Bacteroidota ratio was reduced following the administration of GTP. The contents of Faecalibacterium and Bacteroides were increased, while the contents of Escherichia_Shigella and Dorea were reduced after GTP treatment. Furthermore, GTP were degraded and utilized by gut microbiota to produce SCFAs and reducing pH value. GTP regulated the composition of the gut microbiota and has the potential to act as a prebiotic, with the possibility of its use as a functional food.